The relationships between school climate and adolescent mental health and wellbeing: A systematic literature review - Aldridge, Jill; McChesney, K. (Pergamon, 2018)
© 2018 Elsevier Ltd Promoting adolescent mental health is a global priority, and schools have an important role to play. This systematic mixed- methods literature review examined relationships between the psychosocial school climate and adolescents’ mental health, mapping the scope and quality of recent research. Forty-eight relevant primary studies published in 2000–2017 were identified and analysed. These studies highlight associations between the school climate and student mental health, although the lack of experimental and longitudinal studies precludes causal claims. Future research directions include: further investigation of the roles of school safety and the psychosocial academic environment on adolescent mental health; greater consistency in the conceptualisation of both school climate and mental health; and clarification of the influence of demographic variables on individual students’ experiences.